A Fractional Integration Model and Testing Procedure with Roots Within the Unit Circle - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana (CESifo GmbH, 2025)
This paper puts forward a general statistical model in the time domain based on the concept of fractional integration. More specifically, in the proposed framework instead of imposing that the roots are strictly on the unit circle, we also allow them to be within the unit circle. This approach enables us to specify the time series in terms of its infinite past, with a rate of dependence between the observations much smaller than that produced by the classic I(d) representations. Both Monte Carlo experiments and empirical applications to climatological and financial data show that the proposed approach performs well.
Keywords: C22; 330; fractional integration; unit roots; testing procedure